What to look for in setting sports training tasks for young players? Analysis of the numerical configuration of players and court size constraints on futsal small-sided games performance difficulty level and player participation - Rigon, T. A.; Drezner, R.; Nogueira, F. F.; Yousefian, F.; Travassos, B.; Dantas, L. E. P. B. T. (International Journal of Performance Analysis in Sport, 2023)
This study aimed to analyse the effects of the numerical configuration of players and court size constraints on futsal small-sided game (SSG) performance difficulty level and player participation. For that, the degree of effectiveness of 6155 offensive actions performed by 59 young players (9-12 years) was investigated in six SSG conditions (2v1a, 2v1b, 2v2, 3v3, 4v2, and 2v4). For the analysis, the raw data were transformed into three indexes: Difficulty Index Without the Ball (DI WOB), Difficulty Index With the Ball (DI WB), and Participation Index (PI). Statistically significant differences (p < 0.05) in the effectiveness of actions performed without the ball and with the ball indicated that the SSGs presented different levels of performance difficulty and player participation. More effective actions were performed in attack superiority configurations and full-court sizes, especially if these constraints were combined, indicating they induced an easier level of play. Court size constraint affected player participation in an inversely proportional fashion (larger spaces of practice induced less player participation). The study results are useful to adjust futsal SSGs for players with different skills. In addition, the adopted action evaluation approach has the potential to become the SSG a performance scanner for the players` current level.